Pengaruh Pengasaman Air Kelapa Dan Air Beras Sebagai Alternatif Pelapukan Media Terhadap Pertumbuhan Jamur Tiram Kelabu (Pleurotus Sajor Caju (Fries) Singer) - Nadia Merisya; - Nurmiati; - Periadnadi (Jurnal Biologi Universitas Andalas, 2014)
Research on the “Effect of acidification of coconut water and rice washing water as an composting alternative of growth medium for gray oyster mushroom (Pleurotus Sajor Caju (Fries) Singer)” was conducted from February to March 2014 in Microbiology Research Laboratory, Biology Departement, Faculty of Mathematics and Natural Science, Andalas University. The research aimed to determine the acidity level that can be used as an alternative for the composting of growth medium of gray oyster mushroom as well as the effect of addition of coconut water and rice washing water for the misellium growth. Adjusting pH of coconut water and rice water showed different effects to the growth myselium and the production medium (baglog). Completely Random Design (CDR) with factorial pattern is the method that used in this research. Acidification of coconut water and rice water with pH 3, pH 4 and normal pH have different effect. The fastest growth of mycelium obtained from coconut water with pH 4 liming treatment (9 days).Key Words : acidification, coconut water, rice washing water, Pleurotus sajor caju, composting alternative